Diazotroph-derived nitrogen release and transfer under varying light intensity: insights from co-culture studies - Hu, Xiaohua; Wen, Zuozhu; Luo, Tingwei; Hong, Haizheng (Frontiers in Marine Science, 2025)
Biological dinitrogen (N2) fixation is a major source of new N to surface seawater, sustaining ocean productivity. However, the fate of diazotroph-derived nitrogen (DDN), specifically its release and transfer, and the factors controlling these processes, remain poorly understood. Here, we established stable co-cultures of the major diazotrophs, filamentous Trichodesmium erythraeum IMS101 and unicellular Crocosphaera watsonii WH8501, with the pico-cyanobacterium Synechococcus sp. WH8102, to explore the intrinsic differences in DDN release and transfer between diazotroph strains. We found that T. erythraeum released similar amounts of DDN as C. watsonii, but had a significantly higher DDN transfer efficiency for supporting Synechococcus cell growth. These results implied a higher bioavailability of fixed N released by T. erythraeum than by C. watsonii. Additionally, we showed that elevated light levels significantly enhanced T. erythraeum DDN release and transfer. Our results provide new insights into the fate of N fixed by different diazotrophs and the environmental factors that control the process.